2020
DOI: 10.1186/s12889-020-08568-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a transtheoretical model - based intervention and motivational interviewing on the management of depression in hospitalized patients with coronary heart disease: a randomized controlled trial

Abstract: Background: Depression is a major risk factor for the morbidity and mortality of cardiovascular disease. A transtheoretical model-based intervention and motivational interviewing have been used to change health risk behaviors and have demonstrated positive effects. To our knowledge, no studies of patients with coronary heart disease (CHD) have used a transtheoretical model-based intervention and motivational interviewing as an intervention to provide dynamic education. Therefore, this study aimed to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…It has since been widely applied for different mental disorders such as depression and eating disorders as well as for enhancing treatment commitment (e.g., medication adherence) in GP practices. A variety of studies showed the effect of motivational interviewing to enhance commitment and further readiness to change (Hettema et al, 2005;Rubak et al, 2005;Azami et al, 2020;Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has since been widely applied for different mental disorders such as depression and eating disorders as well as for enhancing treatment commitment (e.g., medication adherence) in GP practices. A variety of studies showed the effect of motivational interviewing to enhance commitment and further readiness to change (Hettema et al, 2005;Rubak et al, 2005;Azami et al, 2020;Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The participants with heart failure (HF),[ 26 27 28 29 30 31 32 33 ] coronary heart disease (CHD),[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] hypertension (HTN),[ 13 39 40 41 42 43 44 ] coronary artery bypass graft (CABG),[ 20 45 46 47 48 ] myocardial infarctions (MI),[ 17 19 49 50 51 ] patients with pacemaker,[ 52 ] heart valve disease,[ 53 ] and cardiac rehabilitation[ 18 ] were highest and lowest target groups in studied papers, respectively. The detailed characteristics of included studies are revealed in [ Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…TTM as a model of behavior change suggests how individual move through five SOC. [ 5 6 14 15 ] Also, TTM presents ten processes of change and three main constructs to support behavior change. Theory of planned behavior (TPB) considers behavioral intention is the most important determinant of behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transtheoretical Model (TTM) which was developed nearly four decades earlier (12) has been used to understand the smoking behaviour of adolescents in educational setting (13), explain physical activity self-efficacy among African-American adolescents (14), and even to devise interventions to manage depression in hospitalized patients of coronary artery disease in China. (15) Similarly, Theory of Reasoned Action (TRA) (16) has been used to identify perceptions on teenage pregnancies among American Indians (17), devise school-based interventions to promote breakfast consumption among Iranian children (18) and design self-care facility-based intervention for diabetic Iranian women. (19) Similarly, Theory of Planned Behaviour (TPB) and Social Cognitive Theory (SCT) have been applied to various domains of behaviour change including physical activity promotion.…”
Section: Introductionmentioning
confidence: 99%